PENERAPAN RELAKSASI NAFAS DALAM DAN TERAPI MUSIK UNTUK MENGURANGI KECEMASAN PASIEN PRE-OPERASI - Mohammad Rizqi; Ani Syafriati; Suryani (LPPM STIKes Mitra Adiguna, 2026)
Preoperative anxiety is a psychological problem often experienced by patients before surgery and can affect their physiological condition and surgical outcomes. One non-pharmacological intervention that can be done to reduce anxiety is deep breathing relaxation and music therapy. This study aims to determine the application of a combination of deep breathing relaxation and music therapy on the level of pre-operative anxiety of patients in the Central Surgical Installation of Indriati Hospital, Solo Baru. The study used a descriptive case study design on four patients undergoing surgery. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) before and after the intervention. The intervention was given for approximately 10 minutes by combining deep breathing relaxation techniques and music therapy. The results showed that all respondents experienced a decrease in anxiety levels from the moderate category with an average score of 22.5 to the mild category with an average score of 12.5 after the intervention. The combination of deep breathing relaxation and music therapy provides a relaxing effect, increases comfort, and helps patients feel calmer before undergoing surgery. This intervention is easy to implement and can be used as an independent action by nurses to reduce pre-operative anxiety in patients.